Obstetric anal sphincter injury in adolescent mothers - Henry H. Chill; Michal Lipschuetz; Eyal Atias; Tzvika Shimonovitz; David Shveiky; Gilad Karavani (BMC, 2021)
Abstract Background Obstetric anal sphincter injury (OASI) is a debilitating complication of vaginal delivery which has yet to receive ample attention in adolescents. The aim of this study was to describe risk for OASI in adolescent mothers compared to adults. We further attempted to compare risk factors for OASI between these two age groups. Methods We performed a retrospective cohort study between 2003 and 2019. Primiparous women who delivered vaginally, 21 years and younger were compared to women ages 26-35. Excluded were preterm, multifetal, non-vertex, cesarean deliveries as well as intrauterine fetal death. Rate of OASI as well as obstetric and labor characteristics of women with OASI, were compared between groups. Finally, risk factors were assessed for each group separately. Univariate and multivariate logistic regression model were performed. Results Final analysis was performed on 5113 nulliparous adolescents and 13,845 nulliparous in the 26-35 age group. Allocation to study groups was according to OASI - Sixty-seven adolescents (1.3%) had a 3rd or 4th degree perineal tear and were defined as the OASI group, while 5046 patients (98.7%) did not have such a tear. In the adult group, 199 out of 13,845 patients (1.4%) were diagnosed with OASI. Occurrence of OASI did not differ between groups (p = 0.510). Comparison of women with OASI in the adolescent group vs. adult group found differences with regard to operative vaginal delivery, (20.9% vs. 36.2%, respectively; p = 0.023) and meconium stained amniotic fluid (9.1% vs. 21.3%, respectively; p = 0.027). Following multivariate analysis the only parameter independently associated with OASI in the adolescent age group was head circumference ≥ 90th percentile with an adjusted odds ratio of 3.08 (CI 1.48-6.38, p = 0.003). In the adult group the similar analysis revealed operative vaginal delivery (OR = 2.44, CI 1.72-3.47, p < 0.001) and a birthweight≥90th percentile (OR = 2.23, CI 1.19-4.18, p = 0.012) to be independent risk factors for OASI. Conclusion Adolescents have similar risk for OASI compared to adults but differ in risk factors leading to OASI. Head circumference ≥ 90th percentile was found to be associated with OASI in this age group.